PARTICIPATION OF BRAYUT VILLAGE SOCIETY ON THE DEVELOPMENT OF TOURISM VILLAGE BASED ON ECOTOURISM AS A REPRESENTATION OF HUMAN NATURE PHILOSOPHY - Fadhila Rachmadani (Jurnal Kawistara, 2018)
The environmental crisis is a problem that has a serious impact for life on the earth. Drought, climate change, and environmental degradation are the part of the environmental crisis which is caused by human intervention to the environment. This paper is discussesed a study case about participation of Brayut Village society, Pendowoharjo, Sleman, Yogyakarta Special Region in developing of tourist village based on ecotourism. Brayut has developed the village based on ecotourism in order to maintain the natural conservation which is concern on agriculture. The participation of Brayut society in the implementation of ecotourism is represents environmental awareness attitude which is deliver a point to the public about a response to the environment crisis in Pendowoharjo, Sleman, Yogyakarta Special Region. Also as a reflection of human nature philosophy that shows a human responsibility to the environment.